Internally generated decadal cold events in the northern North Atlantic and their possible implications for the demise of the Norse settlements in Greenland - Moreno-Chamarro, Eduardo; Zanchettin, Davide; Lohmann, Katja; Jungclaus, Johann H. (Geophysical Research Letters, 2015)
We attribute and describe the governing mechanisms of decadal cold excursions in the subpolar North Atlantic of similar amplitude and duration to cold events reconstructed from climate-proxies during the last millennium detected in an ensemble of three transient and one unperturbed climate simulation. The cold events are attributed to internal regional climate variability, with varying external forcing increasing their magnitude and frequency. The underlying general mechanism consists of a feedback loop initiated by a weakening of the North Atlantic subpolar gyre, which induces persistent colder and fresher surface conditions in the Labrador Sea and, eventually, a deep convection shutdown. We thus exclude a hemispheric climate reorganization or a weak ocean overturning circulation as necessary trigger for such events. An associated northeastward atmospheric cold advection over the Labrador Sea deteriorates local living conditions on south Greenland, essential for the sustainability of the Norse settlements.